Surgical treatment of late aortic prosthetic valve endocarditis: 19 years’ experience - Yayla, Tuncer Eylem; Taylan, Adademir; Serpil, Tas; Bal, Polat Ebru; Antal, Dönmez Arzu; Adnan, Ak; Mustafa, Akbulut; Bulbul, Serhat; Aksut, Mehmet; Altug, Tuncer (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Aim of the study: We retrospectively analyzed the results of operations conducted for aortic prosthetic valve endocarditis in a single center over 19 years. Material and methods: From February 1992 to January 2011, we performed operations on 27 patients with aortic prosthetic valve endocarditis. Seventeen patients (63.0%) were male, and the mean age was 39.1 ± 14.2 (16-67) years. Blood cultures were positive in 11 patients (40.7%), and the most commonly identified microorganism was Streptococcus (7 patients, 25.9%). The mean duration of follow-up was 8.6 ± 4.7 years (0.5-18.2), adding up to a total of 136.9 patient/years. Results : Forty procedures were performed on these 27 patients. The most commonly performed procedure was aortic valve replacement with a prosthetic valve – 16 patients (59.3%). Fifteen patients were operated on during the active phase of infection. In-hospital mortality was observed in 11 patients (40.7%). Postoperatively, 12 patients (44.4%) had low cardiac output, 3 (11.1%) suffered from a heart block; none of them required permanent pacemaker implantation. The actuarial survival for 1 and 5 years was 55.6 ± 9.6% and 47.6 ± 9.7%, respectively. Conclusions : Prosthetic valve endocarditis of the aortic valve is a challenging situation for the surgeon. The surgical treatment carries a high mortality rate and long-term survival is low. Among the survivors, however, recurrence and the need for reoperation are unlikely.